末期病人的決策倫理: 三個模式的比較: Decision Making for the Terminally I11: A Comparison of Three Ethical Models - CHAN, Ho-mun (International Journal of Chinese & Comparative Philosophy of Medicine, 2001)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文討論末期病人的決策過程的三個模式，即個人主義、家長主義和家庭本位主義。個人主義過份偏重病人的抉擇，家長主義只強調從專業角度照顧病人的個人最佳利益，這兩個模式均會令家庭角色邊緣化。本丈認為家庭本位主義，更符合東方社會文化，從倫理角度來看亦較其他兩個模式可取。 This paper critically examines the liberal, the medical paternalist, and the familial models of decision making for the terminally ill. It is argued that the liberal model is excessively patient centered while the medical paternalist model overemphasizes the role of the physician. The paper concludes that since both models marginalize the role of the family in the decision-making process, they are morally inadequate and not suitable for societies with strong family ethics, particularly those in Asia. The liberal model is predominant in the United States. According to this model, a competent patient can express in an advance directive her prior wish of how she is to be treated when she lapses into incompetency. In the absence of an advance directive or in cases where the directive is vague or ambiguous, the surrogate decision-making process will be invoked, which is normally a procedure in which the family makes the decision on the patient's behalf. In this process, the family serves to assist the incompetent patient to exercise her self-determination by figuring out and then following her counterfactual choice in accordance with the substituted judgment standard. If it is impossible to arrive at a decision by following this standard, the family, with the assistance of the physician, will follow the standard of best interests to promote the well-being of the patient. In sum, in the process of surrogate decision making, only the individual choice and interests of the patient are a matter of concern. Thus, the liberal model is entirely patient-centered. The role of the family is marginalized in the sense of being subordinated to the (previous or counterfactual) choice and interests of the patient. The family therefore becomes a "shadow" of the patient with no independent status and is deprived of its self-sufficiency. In the United Kingdom, medical paternalism is more influential. There is a preference for a code of practice to legislation for advance directives, and the prevalence of the best interest standard. Yet, unlike the liberal model, the best interests of the patient are not determined by the family in accordance with the standard of a reasonable person. Rather the doctor is expected to make decision for the patient in accordance with a responsible and competent body of relevant professional opinion in determining the patient's best interests. Though the family will often be consulted, the principal decision maker is the physician. So the role of the family is also marginal in this model. In Asian societies, e.g., Japan, Mainland China and Hong Kong, the family plays a fundamental role in the decision making for the terminally ill, so the model of familialism prevails. In these societies, it is common that the patient will not be informed directly of her terminal illness by the physician. The decision for the incompetent patient is regarded not as an individual but a family decision, and the dying process is viewed a sharing process, the last journey that the patient undergoes together with her significant others. In the familial model, the decision for a terminally ill patient is regarded not entirely as an individual matter because other members will be affected by the patient's choice. Should a son merely consider the wishes or the best interests of his father without considering the burden of care and the feelings of his mother while his father is going through the last stage of his life? Should the mother also consider the financial burden that her son might have to bear for his father if he were to be kept alive at all costs? Such issues would not have a place in the liberal and the medical paternalist models, for what matters is only the choice or the best interests of the patient. On the contrary, due considerations are given to these issues in the familial model, which makes it more plausible than the other two models. DOWNLOAD HISTORY | This article has been downloaded 15 times in Digital Commons before migrating into this platform.